2009
DOI: 10.1371/currents.rrn1011
|View full text |Cite
|
Sign up to set email alerts
|

Fitness of Pandemic H1N1 and Seasonal influenza A viruses during Co-infectionEvidence of competitive advantage of pandemic H1N1 influenza versus seasonal influenza

Abstract: On June 11, 2009 the World Health Organization (WHO) declared a new H1N1 influenza pandemic. This pandemic strain is as transmissible as seasonal H1N1 and H3N2 influenza A viruses. Major concerns facing this pandemic are whether the new virus will replace, co-circulate and/or reassort with seasonal H1N1 and/or H3N2 human strains. Using the ferret model, we investigated which of these three possibilities were most likely favored. Our studies showed that the current pandemic virus is more transmissible than, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 10 publications
2
25
0
Order By: Relevance
“…Induction of proinflammatory cytokines was also markedly increased in the lungs of mice and macaques following 2009 S-OIV infection compared with seasonal H1N1 virus infection (54). Aerosol transmission between ferrets was comparable to (50,54,55), or slightly less efficient than (49), seasonal H1N1 viruses. Miniature pigs displayed few disease symptoms after infection with 2009 S-OIV, despite high levels of viral replication in the lungs (54).…”
Section: S-oiv (H1n1) During March and April Of 2009mentioning
confidence: 91%
See 2 more Smart Citations
“…Induction of proinflammatory cytokines was also markedly increased in the lungs of mice and macaques following 2009 S-OIV infection compared with seasonal H1N1 virus infection (54). Aerosol transmission between ferrets was comparable to (50,54,55), or slightly less efficient than (49), seasonal H1N1 viruses. Miniature pigs displayed few disease symptoms after infection with 2009 S-OIV, despite high levels of viral replication in the lungs (54).…”
Section: S-oiv (H1n1) During March and April Of 2009mentioning
confidence: 91%
“…In mice, ferrets, and nonhuman primates, 2009 S-OIV replicated efficiently in the upper and lower respiratory tracts and induced more pronounced lung pathology than seasonal H1N1 viruses (49,50,54,55). Induction of proinflammatory cytokines was also markedly increased in the lungs of mice and macaques following 2009 S-OIV infection compared with seasonal H1N1 virus infection (54).…”
Section: S-oiv (H1n1) During March and April Of 2009mentioning
confidence: 95%
See 1 more Smart Citation
“…Several studies have tried to evaluate the likelihood of such reassortant events to occur, as well as the pathogenicity and/or transmissibility of progeny viruses in animal models. [31][32][33][34] Perez et al coinfected ferrets with an A(H1N1)pdm09 virus and A(H1N1) or A(H3N2) seasonal human viruses. The results of this study showed that there was no selective advantage for novel reassortants to be generated in this model system and in fact the A(H1N1) pdm09 virus dominated over both seasonal counterparts.…”
Section: Reassortment In Experimental Modelsmentioning
confidence: 99%
“…The results of this study showed that there was no selective advantage for novel reassortants to be generated in this model system and in fact the A(H1N1) pdm09 virus dominated over both seasonal counterparts. 32 Two additional teams demonstrated the possibility of reassortment between A(H1N1)pdm09 and human seasonal viruses in vitro. In both studies, and in contrast with the earlier work, reassortant progeny viruses were generated, and these turned out to be more virulent than their parental strains in the ferret model.…”
Section: Reassortment In Experimental Modelsmentioning
confidence: 99%